Tunnel Operations in the Israel Defense Forces: Adapting the Warrior Ethos to Post-Heroic Conflict. Issue 2 (April 2022) - Stern, Nehemia; Ben-Shalom, Uzi; Gold, Niv; Berger, Corinne; Antonovsky, Avishai; Peleg, Dvir
This study presents an empirically grounded account of tunnel combat operations in the Israel Defense Forces (IDF) within the context of "post-heroic" warfare. Current scholarship on "post-heroism" has viewed the technological and professional standards of contemporary military conflicts as distancing the individual combatant from the modern battlefield. Little attention has been given however to the ways in which soldiers themselves experience and adapt to post-heroic conditions. Findings based on in-depth semistructured interviews with 17 IDF tunnel combatants show these soldiers actively reinterpreting the strategic importance placed on distancing the warrior from the battlefield. This exploratory article suggests that an individual "warrior ethos" still resonates amid the professional and technological contours of post-heroic (underground) conflicts. By presenting a novel account of contemporary tunnel warfare from the perspective of the combatants themselves, this research sheds new light on the different personal dimensions that impact post-heroic military operations.